THE USE OF WANDA PA'U TRADITIONAL DANCE IN LEARNING BASIC PHYSICS FOR BIOLOGY EDUCATION STUDENTS AT UNIVERSITAS FLORES - Yuliana Yenita Mete; Ainun Jariyah; Yosefina Angelina Mili (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to reveal the use of Wanda Pa'u traditional dance to improve students’ learning interests and understandings in learning basic physics in Biology Education Study Programs, Universitas Flores. This research was classroom action research (CAR) consisting of four stages: planning, implementation, observation, and reflection. The data collection was carried out through observation,interviews, questionnaires, tests, and documentation. Then, the data were analyzed quantitatively and qualitatively. The results showed that the students’ learning interest at pre-action was 52.25% (low category). Then, in the first cycle, it increased to 71.75% (medium category), and in the second cycle, it became 81.5% (high category). The average score of students’ understanding was 45% at pre-action, 65% in cycle I, and 96.4% in cycle II. The conclusion was that the use of Wanda Pa'u as a learning medium increased the students’ learning interests and understandings at Biology Education Study Program Universitas Flores.